Profitability determinants analysis of banks based on ratio analysis - XU, XIN (2018)
Using the dynamic two-stage system Generalized Methods of Moments (SGMM) method, this paper researches the determinants of the profitability for China's commercial banks in time from 2011 to 2017. The profitability is measured by average return on assets (ROAA) and average return on equity (ROAE) respectively. Referring to a variety of literatures at home and abroad, first of all, the overall status of existing commercial banks in China is analysed. In addition, the factors explaining the profitability for commercial banks are divided into bank-specific (such as asset quality indicators, capital indicators, operational indicators, liquidity indicators, and bankruptcy indicators, etc.) and macroeconomic factors (such as GDP growth rate, unemployment, inflation). Finally, data selected from China’s commercial banks for the period 2011-2017 is employed to conduct relevant analysis and dynamic modelling of these factors on ROAA as well as ROAE. The empirical results show that the profitability in banking sector exists persistently, which confirms that the dynamic system Generalized Methods of Moments (SGMM) model is applied to the unbalanced panel data. Taking ROAA and ROAE as the dependent variables, the models obtained empirical conclusions that the banks are significantly affected by the external macroeconomic environment. In addition, some bank-specific factors have different degrees of impact on the profitability of commercial banks.